The investigation of EFL teachers’ professional and social competence in english online teaching (In Utilizing ICT Media) - Hilmiyah Akib; Andi Roy (Institute of Computer Science (IOCS), 2023)
Therefore, this research aimed to describe EFL teachers’ professional competence in terms of developing learning material, developing professionalism, and utilizing ICT media, as well EFL teachers’ social competence in terms of being inclusive and objectively and communicating effectively in English online teaching. This research applied a qualitative descriptive as the research design. In collecting the data, the researcher applied observation, interview, and documentation. The data was then processed by using the technique of data analysis based on Miles and Huberman involved data reduction, data display, and conclusion drawing. The results showed that EFL teachers’ professional competence in developing learning material indicated two categories; semi-material development, and non-material development. Then, EFL teachers’ professional competence in developing professionalism continuously indicated that the teachers did self-evaluation, and did self-improvement. In utilizing ICT media, the results indicated that the EFL teachers used mono-ICT media and multi-ICT medias in teaching online. Meanwhile, the results for EFL teachers’ social competence indicated that EFL teachers implemented inclusively and objectively as well communicating effectively with the students during teaching online.